2015
DOI: 10.1007/s00253-015-6776-x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Saccharomyces cerevisiae strains as biotherapeutic tools: is there room for improvement?

Abstract: The probiotic yeast Saccharomyces cerevisiae var boulardii is widely used as a low cost and efficient adjuvant against gastrointestinal tract disorders such as inflammatory bowel disease and treatment of several types of diarrhea, both in humans and animals. S. boulardii exerts its protective mechanisms by binding and neutralizing enteric pathogens or their toxins, by reducing inflammation and by inducing the secretion of sIgA. Although several S. cerevisiae strains have proven probiotic potential in both huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 65 publications
(134 reference statements)
2
50
0
4
Order By: Relevance
“…S. boulardii stimulates host immune systems and intestinal enzymes that enhance nutrient digestion and absorption (24). In support of these distinctive mechanisms, the live yeast S. boulardii is used extensively as a probiotic and is often marketed as a dietary supplement (10,25). However, S. boulardii belongs to the group of simple eukaryotic cells; it thus differs from bacterial probiotics that are prokaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. boulardii stimulates host immune systems and intestinal enzymes that enhance nutrient digestion and absorption (24). In support of these distinctive mechanisms, the live yeast S. boulardii is used extensively as a probiotic and is often marketed as a dietary supplement (10,25). However, S. boulardii belongs to the group of simple eukaryotic cells; it thus differs from bacterial probiotics that are prokaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the previous reports indicated that this yeast decreased the incidence of antibiotic-associated diarrhea (9,26) and diminished the risk of recurrence of Clostridium difficile-associated and Crohn's diseases (27). S. boulardii was also used for lactose intolerance, urinary tract infections (UTIs), vaginal yeast infections, high cholesterol levels, fever blisters, and teenage acne (25,28,29). Considering the beneficial aspects, the present study was undertaken to isolate and characterize the yeast S. boulardii and investigate its ability to tolerate different concentrations of bile salt, cell hydrophobicity, antioxidants, autoaggregation activity, and simulated gastrointestinal digestion.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the PGM2 mutation was enriched due to selection of S. boulardii in the natural habitat (sugar-rich fruits in tropical areas). KEYWORDS Saccharomyces boulardii, galactose, PGM2, genome editing S accharomyces boulardii was first isolated from the surfaces of mangosteen and lychee fruits, and this yeast has been proven to be an effective dietary supplement for treating diarrhea (1,2). S. boulardii has been extensively studied for its probiotic effects against gastrointestinal tract disorders (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…cerevisiae (and DMF) as probiotic is interesting, it should, in the light of our study, be carefully implemented after further investigations into its effect and safety[22]. Our study showed that a higher S .…”
Section: Discussionmentioning
confidence: 81%